Innsbruck Teleportation Experiment in the Wigner Formalism: A Realistic Description Based on the Role of the Zero-Point Field - Casado, Alberto; Guerra, Santiago; Plácido, José (Frontiers in Physics, 2020)
In this paper, an undulatory description of the Innsbruck teleportation experiment is given, grounded in the role of the zeropoint ﬁeld. The Wigner approach in the Heisenberg picture is used, so that the quadruple correlations of the ﬁeld, along with the subtraction of the zeropoint intensity at the detectors, are shown to be the essential ingredients that replace entanglement and collapse. This study sharply contrasts with the standard particle-like analysis and opens the possibility for the understanding of the hidden mechanism for teleportation, relying on the vacuum amplitudes as hidden variables.